Characteristic flavor of Antarctic krill (Euphausia superba) and white shrimp (Penaeus vannamei) induced by thermal treatment. (1st June 2022) - Bai, Jing; Fan, Yan; Zhu, Lulu; Wang, Yanchao; Hou, Hu
Highlights: The taste-active compounds in steaming and boiling shrimp meat were analyzed. The volatile flavor compounds of shrimp meat induced by thermal were studied. The kind and content of flavor compounds were changed after thermal treatment. Aldehydes, pyrazines and ketones contribute to the characteristic shrimp flavor. Abstract: For the good acceptance and preference of heated shrimp, characteristic flavor composition analysis was necessary. The sensory evaluation, electronic tongue, electronic nose, and gas chromatography-ion mobility spectrometry were employed in this study. After steaming or cooking, the sensory scores of Antarctic krill (KM) and white shrimp (PM) were significantly increased, and five basic tastes were remarkably changed by electronic tongue analysis. Free glycine level increased from 86.48 to 687.12 mg/100 g in PM after steaming, but no significant changes in KM. 5′-nucleotides in heated PM were higher than those in heated KM. In two kinds of shrimp, inorganic ions and lactic acids contents exhibited the decrease trends after cooking, and the response intensities of S4, S5, and S6 showed increase trends after steaming. Nonanal, benzaldehyde, (Z)-3-hexen-1-ol, 1-8-cineol and limonene were produced by thermal treatment. Therefore, characteristic flavor formation was related to thermal treatment.